Predictors of Mammalian Diversity in the New York Metropolitan Area - Bradfield, Angelinna A.; Nagy, Christopher M.; Weckel, Mark; Lahti, David C.; Habig, Bobby (Frontiers in Ecology and Evolution, 2022)
Urbanization can have profound consequences for mammalian biodiversity and is thought to contribute to patterns of species richness and community composition. Large cities can be particularly challenging environments for mammals because these habitats are often impacted by anthropogenic perturbations, including high human population density, fragmented habitats, and extensive human development. In this study, we investigated mammalian species richness, Shannon-Wiener diversity, and evenness in the most densely populated region in the United States: the New York metropolitan area. Specifically, we deployed camera traps from 2015-2019 to investigate six drivers of mammalian diversity across 31 greenspaces: (1) human population density, (2) patch size, (3) habitat type, (4) surrounding land cover, (5) geographical barriers to dispersal, and (6) habitat heterogeneity. We found that mammal community composition is largely influenced by a multitude of anthropogenic factors. Specifically, mammal species richness was higher in greenspaces with larger patch sizes and lower in greenspaces surrounded by more development. Moreover, Shannon-Weiner diversity and evenness were higher in urban natural landscapes than human-altered landscapes. In a subset of data that only included carnivores, we found that carnivore Shannon-Wiener diversity was higher in urban natural habitats and in sites with lower human population densities. Finally, we found that geographical barriers to dispersal contributed to both patterns of mammalian diversity and patterns of carnivore diversity: mammal taxa richness, Shannon-Weiner diversity, and evenness were all significantly higher on the continent (Bronx/Westchester) than on Long Island. These results suggest that preserving urban greenspaces is important for maintaining both mammalian and carnivore biodiversity and that management of mammals in cities should concentrate on maintaining large, connected, natural greenspaces.